High Sequence Variations in Mitochondrial DNA Control Region among Worldwide Populations of Flathead Mullet Mugil cephalus - Jamandre, Brian Wade; Durand, Jean-Dominique; Tzeng, Wann-Nian (International Journal of Zoology, 2014)
The sequence and structure of the complete mtDNA control region (CR) of M. cephalus from African, Pacific, and Atlantic populations are presented in this study to assess its usefulness in phylogeographic studies of this species. The mtDNA CR sequence variations among M. cephalus populations largely exceeded intraspecific polymorphisms that are generally observed in other vertebrates. The length of CR sequence varied among M. cephalus populations due to the presence of indels and variable number of tandem repeats at the 3′ hypervariable domain. The high evolutionary rate of the CR in this species probably originated from these mutations. However, no excessive homoplasic mutations were noticed. Finally, the star shaped tree inferred from the CR polymorphism stresses a rapid radiation worldwide, in this species. The CR still appears as a good marker for phylogeographic investigations and additional worldwide samples are warranted to further investigate the genetic structure and evolution in M. cephalus.